Bamboo Based Natural Packaging: Indian Scenario - Salam, Kamesh (Indian Horticulture, 2024)
Bamboo is a strategic resource growing across the world particularly in Northeast India, which can be processed in various ways to produce different products, to be used as substitutions for the existing plastic material as it is biodegradable. Before the existence of plastic, there were products made from bamboo and packaging was also made from bamboo. This begs the question, is this packaging sustainable and how it can substitute other material. Traditionally, in India bamboo basket weaving has rich cultural identity and used in all household applications mainly in packing which is now needed to bring into the modern packing for variousproducts. The paper discuss the sustainable development and uses of bamboo packaging in Northeastern region.